Conceptual Categories Expressed by Terms of Astrophysics - A. A. Levit (Научный диалог)
The results of research in the field of terminology studies are presented. The content of synonymic terms conceptual category , type of concept , category of mental construct that are the key terms in this study is revealed. The typology of conceptual categories is discussed. The existing classifications of types of concepts, verbalized by the terms are given. The main objective of the study is a detailed examination of the typology of concepts introduced in the terminology of astrophysics. Attempt to divide the terms into categories distinguished to this area of scientific knowledge is made. The percentage of terminological lexical units that appear in each of the categories is given. The paper identifies the most and the least frequent conceptual categories, which are expressed in the terms belonging to a given field of scientific knowledge. It is argued that the difference in the percentage of verbalization of the types of concepts are determined primarily by specific sub-language for special purposes, by example of which the study is conducted. The importance of studying the typology of terminological units for the analysis of the system organization of specialized vocabulary is proved. The prospects for further research in this direction are revealed. Material for analysis were Russian terminological lexical units extracted from terminological dictionaries and encyclopedias, as well as articles on specialized Internet-resources.